STUDY OF THE INFLUENCE OF CRACKS ON THE BEARING CAPACITY OF REINFORCED CONCRETE PLATES USING THE PRINS CALCULATION COMPLEX - K. R. Aydemirov; V. P. Agapov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. In order to determine a residual safety factor, a finite element method is considered for determining the bearing capacity of reinforced concrete plates having defects in the form of cracks.Method. The methodology is based on the use of structural calculation algorithms that take physical nonlinearity implemented in the PRINS programme into account. These algorithms assume the use of the same computational scheme in the process of solving the problem. However, the specificity of the task consists in considering differences between the calculation schemes of the initial structure and the structure having cracks.Result. With this in mind, the algorithms of nonlinear structural analysis according to the PRINS programme are supplemented with an option that allows the parameters of the design scheme to be changed in an end-to-end calculation process. Multilayer finite elements are used to study the load-bearing capacity of reinforced concrete plates, each having a specific material package. The modernisation of the design scheme in this case consists in replacing one package of materials with another. The input file of the PRINS programme is supplemented by a description of cracks with an indication of their location and all other relevant characteristics. Examples of problems arising when determining the bearing capacity of a plate with defects in the form of cracks under various boundary conditions are given.Conclusion. The problem of determining the bearing capacity of reinforced concrete plates with defects in the form of cracks can be effectively solved using a reconfigurable design scheme for end-to-end calculation. In the event of defects appearing in the form of cracks, this will enable operational services to monitor changes in the bearing capacity of buildings and structures containing reinforced concrete plates, as well as to determine the operability of structures and make substantiated decisions in case of repair.